The price responsiveness of energy demand in the Philippine food processing sector - Ranada, Julie G (The Philippine Review of Business and Economics, 1985)
This study attempts to derive reliable estimates of the price elasticity of demand for energy and the elasticities of substitution among labor, capital and energy in Philippine production. Three different methods of increasing complexity are fitted to data for firms employing twenty or more workers, based on annual surveys of the National Census and Statistics Office. The food processing sector in Philippine manufacturing was chosen as the testing ground for the types of analyses proposed. Findings show a greater degree of price responsiveness of energy demand in the 1970-78 period for the food processing industry than what previous aggregation studies have reported. Furthermore, energy, labor and capital are found to be substitutes for each other.